Faktor Determinan yang Mempengaruhi terjadinya Postpartum Blues pada Ibu Nifas - Nila Marwiyah; Deni Suwardiman; Hanna Kurnia Mutia; Nida Ayu Alkarimah; Resti Rahayu; Nuraeni Nuraeni; Ita Uzzakiyyah (Faletehan Health Journal, 2022)
Postpartum blues is a temporarily depression period which may happen during the first few days of puerperium. The condition, if not resolved, may cause mothers depression and disturb the growth and development of the newborns. This study aimed to identify the dominant factor affecting postpartum blues incidents in puerperium mothers. This study used correlational method with cross-sectional approach. The samples were 68 respondents who were selected by consecutive sampling technique. Edinburgh Postnatal Depression Scale (EDPS) was utilized to determine the postpartum incidents, Multidimensional Scale of Perceived Social Support (MSPSS) to measure social supports, and Breaf COPE scale to measure coping. The data was analyzed by using multiple regression. The results showed that the mean of postpartum blues was 8.09 (SD 4.78). The related factors are age, income, delivery type, delivery preparedness, and social support. Age had the strongest correlation and significantly contribute to postpartum blues incidents (Beta 0.347, p<0.01). The efforts of increasing postpartum blues early detection, health education, and social support for mothers with postpartum blues were required.